2004
DOI: 10.1182/blood-2004-05-1798
|View full text |Cite
|
Sign up to set email alerts
|

KSHV viral cyclin binds to p27KIP1 in primary effusion lymphomas

Abstract: Primary effusion lymphomas (PELs) represent a unique non-Hodgkin lymphoma that is consistently infected by Kaposi sarcoma herpesvirus (KSHV). PEL cells express high levels of the cell cycle inhibitor p27 KIP1 and yet proliferate actively. KSHV genome encodes a viral cyclin homolog, v-cyclin, which has previously been implicated in down-regulation of p27 KIP1 levels. To address how PEL cells can tolerate high p27 KIP1 levels, we investigated functional interactions between v-cyclin and p27 KIP1 using PEL-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…K cyclin expression was induced with 1 mM IPTG (isopropyl-␣-D-thiogalactopyranoside). Culture of U2-OS cells and transfection has been previously described (16,23). The U2-OS-K cyclin cell line (U2-OS-K) was a kind gift from Heike Laman (Division of Virology, Department of Pathology, University of Cambridge) and Flag-tagged K cyclin expression was induced with 5 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…K cyclin expression was induced with 1 mM IPTG (isopropyl-␣-D-thiogalactopyranoside). Culture of U2-OS cells and transfection has been previously described (16,23). The U2-OS-K cyclin cell line (U2-OS-K) was a kind gift from Heike Laman (Division of Virology, Department of Pathology, University of Cambridge) and Flag-tagged K cyclin expression was induced with 5 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
“…For immunohistochemical analysis, transfected cells were fixed with 3.5% (wt/vol) paraformaldehyde and permeabilized with 0.1% Triton X-100 for 5 min. Immunofluorescence labeling was performed as previously described (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…v-CYC interacts with cyclin dependent kinase 6 (CDK6) and promotes G1-S progression (Godden-Kent et al, 1997;Swanton et al, 1997). The Cyclin D-CDK6 complex is to function to exit from G0 to G1 phase (Laman et al, 2001) and the v-cyc/CDK6 complex is resistant to inhibition by CDK inhibitors by p16, p21 and p27 (Jarviluoma et al, 2004). Thus, its real function has not been elucidated and it was reported that ectopic or overexpression of c-CYC evokes rather cell/DNA damage (Koopal et al, 2007).…”
Section: Viral Cyclin (V-cyc)mentioning
confidence: 99%